PEMBATAS KECEPATAN DATA PADA PC-ROUTER BERBASIS LINUX MENGGUNAKAN DISIPLIN ANTRIAN HIERARCHICAL TOKEN BUCKET (HTB) - Hari Siswantoro (Jenderal Soedirman University, 2007)
A common problem which occurred on a network router is bottle-neck phenomenon. This problem appear if the router is connecting high speed network (e.g. a 100 Mbps fast ethernet LAN) to low speed network (e.g. 512 kbps DSL internet line). To avoid traffic congestion, there must be a mechanism to control the link sharing. This paper discusses the use of Hierarchical Token Bucket (HTB) algorithm, which is embedded in Linux kernel, to share the bandwidth on a link in a controlled fashion. Hierarchical link sharing allows multiple hosts, agencies, or protocol families to share the bandwidth. By implementing the HTB algorithm, we intend to achieve a fair bandwidth sharing according to the policy